Analisis Makna Motivatif Drama Twenty Five Twenty One Karya Kwon Do Eun dalam Perspektif Olahraga Anggar Berbasis Pendidikan Karakter - Syeren Indah Lestari Huda; Intama Jemy Polii; Oldie Stevie Meruntu (Pustaka Digital Indonesia, 2026)
The urgency of this research lies in the importance of examining drama media as a means of building motivation and character education in the younger generation.Amidst various current social challenges, such as declining learning motivation,low mental resilience,and the decline of character values like discipline and responsibility,media are needed that are not only entertaining but also capable of providing positive learning.This study aims to analyze the motivational meaning in the drama Twenty Five Twenty One by Kwon Do Eun from the perspective of fencing sports based on character education.The study uses a qualitative approach with content analysis method. Data sources are in the form of dialogues and scenes relevant to motivational meaning and character education values. Data collection techniques were carried out through watching the drama thoroughly, carefully examining, and recording data related to the focus of the study.Data analysis techniques include data collection, data reduction, data presentation, and drawing conclusions.The results show that there are 6 motivational meanings: (1) motivation to maintain dreams, (2) belief in one's own abilities and hope for the future, (3) positive interpretation of defeat experiences, (4) self-confidence in facing pressure, (5) mental and emotional strengthening,and (6) the importance of solidarity and togetherness. It can be concluded that the drama Twenty Five Twenty One not only functions as entertainment,but also as an educational medium containing motivational messages and character education values relevant to the younger generation. These findings confirm that digital drama as an audiovisual medium is capable of conveying motivational meanings that are aligned with character education values such as persistence,self-confidence,resilience,self-control,empathy,and solidarity.